Unusual Fusion Proteins of HIV-1 - Langer, Simon; Sauter, Daniel (Frontiers in Microbiology, 2017)
Despite its small genome size, the Human Immunodeficiency Virus 1 (HIV-1) is one of the most successful pathogens and has infected more than 70 million people worldwide within the last decades. In total, HIV-1 expresses 16 canonical proteins from only nine genes within its 10 kb genome. Expression of the structural genes gag, pol and env, the regulatory genes rev and tat and the accessory genes vpu, nef, vpr and vif enables assembly of the viral particle, regulates viral gene transcription and equips the virus to evade or counteract host immune responses. In addition to the canonically expressed proteins, a growing number of publications describe the existence of non-canonical fusion proteins in HIV-1 infected cells. Most of them are encoded by the tat-env-rev locus. While the majority of these fusion proteins (e.g. TNV/p28tev, p186Drev, Tat1-Rev2, Tat^8c, p17tev, or Ref) are the result of alternative splicing events, Tat-T/Vpt is produced upon programmed ribosomal frameshifting, and a Rev1-Vpu fusion protein is expressed due to a nucleotide polymorphism that is unique to certain HIV-1 clade A and C strains. A better understanding of the expression and activity of these non-canonical viral proteins will help to dissect their potential role in viral replication and reveal how HIV-1 optimized the coding potential of its genes. The goal of this review is to provide an overview of previously described HIV-1 fusion proteins and to summarize our current knowledge of their expression patterns and putative functions.